Evaluasi Kekuatan Fleksural Resin Komposit Single-Shade dengan Resin Komposit Nanofilled - Fade, Erinna Rizky; Mozartha, Martha; Kesumaputri, Bebbi Arisya; Anastasia, Danica (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2023)
The use of nanofiller in the composite resin improves the mechanical and aesthetic properties and is suitable for anterior and posterior teeth. However, the color-matching procedure is time-consuming and requires professional skills. A single-shade composite resin was developed and claimed to match all tooth colors. Objective to evaluate the flexural strength of single-shade composite resin compared to conventional nanofilled composite resin. Method, his experimental study used specimens measuring 25 x 2 x 2 mm, divided into two groups (n = 10): single-shade composite resin and nanofilled composite resin. Flexural strength was tested using the Universal Testing Machine. The independent t-test was used to analyze the data statistically. Result, The mean value of the flexural strength of single-shade nanofilled composite resin was 110.40 MPa and 106.88 MPa, respectively. Independent t-test results (p > 0.05) showed no significant differences between groups. Conclusion, there was no significant difference in flexural strength between single shade composite resin and conventional nanofilled composite resin.